Vascular pathology in patients with alveolar echinococcosis: framework for assessment and clinical management$da retrospective case series - Gieser, Paula; Merle, Uta; Junghanss, Thomas; Weber, Tim; Stojković, Marija (BMJ open gastroenterology, 2023)
Objective Alveolar echinococcosis (AE) is a parasitic liver disease with infiltrative growth similar to solid organ malignancies. Major vascular damage is frequent and often remains untreated until catastrophic events precipitate. Detailed clinical and radiological assessment is required to guide individualised treatment decisions. Standardised radiological reporting templates of malignancies with profiles resembling AE are candidates for adaptation. Our objectives are to describe vascular pathology in AE and establish a framework for structured evaluation as the basis for treatment decisions and monitoring. - Design Retrospective case series. - Results 69 patients (37.1%) had vascular involvement: portal vein (PV) 24.7%, hepatic vein (HV) 22.6% inferior vena cava (IVC) 13.4%. Significant stenosis/occlusion of vessels was present in 15.1% of PV, in 13.4% of HV and in 7.5% of IVC involvement. Vascular pathology needing specific treatment or monitoring was present in 8.6% of patients. The most frequent clinical presentation was high grade IVC stenosis or occlusion which was seen in 11 patients of the cohort. - Conclusion Advanced AE requires early multidisciplinary assessment to prevent progressive impairment of liver function due to vascular damage. The focus at first presentation is on complete evaluation of vascular (and biliary) involvement. The focus in non-resectable AE is on prevention of vascular (and biliary) complications while suppressing growth of AE lesions by benzimidazole treatment to improve the quality of life of patients. We developed a framework for standardised vascular assessment and follow-up of patients with AE to recognise and treat complications early.
Frontdoor des Artikels: "First published August 11, 2023, online issue publication February 12, 2024"
Gesehen am 08.04.2024